Development and Validation of UV-Spectroscopic Method for Estimation of Niacin in Bulk and Pharmaceutical Dosage Form - Indranil Chanda, Ripunjoy Bordoloi, Debarupa D. Chakraborty, Prithviraj Chakraborty, Smriti Rekha Chanda Das (Journal of Applied Pharmaceutical Science, 2017)
A novel, simple, specific and economic UV Spectrophotometric method has been developed using ethanol as solvent to estimate niacin content in bulk and pharmaceutical dosage formulation. The λmax of niacin was found to be 262 nm. Linearity in the concentration range of 01-19μg/ml was found to be exhibiting good correlation coefficient (R2=0.9991). The developed method was validated statistically to demonstrate linearity, accuracy, precision, LOD and LOQ. The validation parameters were selected as per the ICH [Q2 (R1)] guideline. The results of the study proved the applicability of the present method in routine analysis of niacin in bulk as well as in the formulation.
Keywords: Niacin, UV Spectrophotometric, Method development, validation, ICH guideline.